Studies on genotypic response of nutmeg to softwood grafting - B P Patil, A J Kelaskar, V S Sawant, P M Haldankar, G D Joshi, B M Jamadagni (Journal of Spices and Aromatic Crops, 2003)
An experiment was conducted to study the success rate of softwood grafting in 22 female, 12 hermaphrodite and S male nutmeg genotypes. The variation among genotypes for sprouting, survival and growth parameters was statistically significant. The magnitudes of GeV, pev, habitability and genetic advance were low for sprouting and survival of nutmeg grafts. The graft survival has strong negative correlation with leaf width. Maximum graft sprouting was associated with the faster production of new leaves with less breadth and longer petiole. The genotypes, N66, N24, N61, Nl, NS, N29, N38 and N49 gave the best response to grafting.